SUSTAINABLE DEVELOPMENT MANAGEMENT OF THE GRASSLAND AGROECOSYSTEM IN THE CONTEXT OF BIODIVERSITY CONSERVATION AND IMPROVEMENT OF PERMANENT GRASSLAND - Pompilica IAGARU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2015)
The agricultural enterprise, seen from a sustainable development perspective, operates within an ecosystem, and aims to achieve a harmonious interpenetration and integration with it. The way in which this interpenetration and integration is realized depends on the level achieved by its performances, which requires the adoption of policies and strategies and the economic organization of biotechnical processes. The paper emphasizes an interdisciplinary approach to issues like management and sustainable development of the grassland agro ecosystem and shows that promoting ecological techniques in the grassland agro ecosystem can ensure its versatility. All these supported by obtaining appropriate pastoral values, namely biodiversity conservation and improvement of meadows, and knowing that Romania has a variety of floral structures with high biodiversity indices.